Kewenangan Komisi Yudisial dan Dewan Perwakilan Rakyat Dalam Pengangkatan Hakim Agung - Diah Savitri (Jurnal Cita Hukum, 2013)
Abstract: Judicial Commission and House of Representative Authority in choosing Judges of Supreme Court. House of Representative Authority in choosing Candidate of Supreme Court Judges as meant By the Act related to Judicial Commission and Act of the Supreme Court are not compatible with the provision as mentioned in article 24 A (3) Constitution of 1945. It was Constitutional Court through its decision Number 27/PUU-XI/2013 that revised the meaning of “to agree”. It revised also the provision that oblige of Judicial Commission to propose three Candidate Supreme Court Judge in every process carried out in Parliament. This provision is difficult to comply by the Commission therefore Constitutional Court has regulate that the Judicial Commission only nominate one candidate in every selection made. Abtrak: Kewenangan Komisi Yudisial dan Dewan Perwakilan Rakyat Dalam Pengangkatan Hakim Agung. Kewenangan DPR untuk memilih calon Hakim Agung seperti yang dimaksud dalam Undang-Undang tentang Komisi Yudisial dan pada dan Undang-Undang tentang Mahkamah Agung ternyata tidak sejalan dengan makna persetujuan yang disebutkan pada Pasal 24A ayat (3) UndangUndang Dasar Negara Republik Indonesia Tahun 1945. Hal ini didasarkan dengan keluarnya putusan Mahkamah Konstitusi Nomor 27/PUU-XI/2013 yang mengubah ketentuan kedua Undang-Undang tersebut menjadi menyetujui. Begitu juga dengan ketentuan yang mengharuskan KY mengajukan 3 (tiga) calon Hakim Agung kepada DPR untuk setiap lowongan Hakim Agung yang dalam praktiknya cukup menyulitkan, maka MK dalam putusannya mengubah kuota calon Hakim Agung yang diusulkan KY kepada DPR menjadi 1 (satu) calon hakim agung untuk setiap lowongan. DOI: 10.15408/jch.v1i2.2993